Research and development in intelligent systems XXXI : Incorporating applications and innovations in intelligent systems XXII - Petridis, Miltos; Bramer, Max (Springer International Publishing, 2014)
The papers in this volume are the refereed papers presented at AI-2014, the Thirty-fourth SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence, held in Cambridge in December 2014 in both the technical and the application streams. They present new and innovative developments and applications, divided into technical stream sections on Knowledge Discovery and Data Mining, Machine Learning, and Agents, Ontologies and Genetic Programming, followed by application stream sections on Evolutionary Algorithms/Dynamic Modelling, Planning and Optimisation, and Machine Learning and Data Mining. The volume also includes the text of short papers presented as posters at the conference. This is the thirty-first volume in the Research and Development in Intelligent Systems series, which also incorporates the twenty-second volume in the Applications and Innovations in Intelligent Systems series. These series are essential reading for those who wish to keep up to date with developments in this important field.